2019
DOI: 10.1177/1553350619881068
|View full text |Cite
|
Sign up to set email alerts
|

Development and Preliminary Validation of a Rabbit Model of Duodenal Atresia for Training in Pediatric Surgical Skills

Abstract: Duodenal atresia is a congenital defect that requires advanced surgical skills. The objective of this study is to present an anatomical defect of duodenal atresia using a rabbit model and evaluate the preliminary experience for the training of surgical skills with pediatric surgeons. Adult white New Zealand male rabbits weighing 3.0 to 4.5 kg were used to create the defect. To simulate the bottom of the dilated blind pouch, the gastric antrum of the rabbit was obliterated using a 2-0 Prolene suture, and the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…This suggests that a minimum number of five laboratory surgeries is definitely needed in the present diamond-shaped anastomosis model, but any further skill development should most probably be monitored under clinical conditions. Our findings are also supported by results from participant feedback forms which are regarded as important tools to gain insights into personal or self-assessment [2,12,13]. The feedback questionnaire used in our study showed that both groups found the task similarly challenging at different stages of the study and the values gradually increased in parallel with the improvement in technical skills (as indicated by the GOALS score).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This suggests that a minimum number of five laboratory surgeries is definitely needed in the present diamond-shaped anastomosis model, but any further skill development should most probably be monitored under clinical conditions. Our findings are also supported by results from participant feedback forms which are regarded as important tools to gain insights into personal or self-assessment [2,12,13]. The feedback questionnaire used in our study showed that both groups found the task similarly challenging at different stages of the study and the values gradually increased in parallel with the improvement in technical skills (as indicated by the GOALS score).…”
Section: Discussionsupporting
confidence: 82%
“…Surgery time is one of the most objective and easily accessible indices of performance [6,12,13,25,26], which was found to be similar to those in clinical practice Fig. 4 Average GOALS score (A), depth perception score (B), bimanual dexterity score (C), efficiency score (D), tissue handling score (E) and overall performance score in the beginner and advanced groups for laparoscopic diamond-shaped anastomosis [22].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations